2020
DOI: 10.3389/fimmu.2020.00710
|View full text |Cite
|
Sign up to set email alerts
|

1-Palmitoyl-2-Linoleoyl-3-Acetyl-rac-Glycerol (PLAG) Mitigates Monosodium Urate (MSU)-Induced Acute Gouty Inflammation in BALB/c Mice

Abstract: Acute gouty arthritis is an auto-inflammatory disease caused by the deposition of monosodium urate (MSU) crystals in joints or tissues. Excessive neutrophil recruitment into gouty lesions is a general clinical sign and induces a pain phenotype. Attenuation of successive periods of neutrophil infiltration might be a beneficial approach to achieve therapeutic efficacy. In this study, the activity of 1-palmitoyl-2-linoleoyl-3-acetyl-rac-glycerol (PLAG) in attenuation of excess neutrophil infiltration was assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…In a previous study, we demonstrated the inhibitory effects of PLAG on tumors and tumor metastasis [45,46]. In addition, in severe inflammatory diseases due to excessive neutrophil infiltration, PLAG treatment provided symptom relief by regulating the movement of neutrophils to inflammatory lesions [47][48][49][50][51][52]. The ability of PLAG to regulate neutrophil infiltration and activity in tumor tissue enables the anti-tumor effect of aPD-L1 to be maximized so that cancer patients can make a complete recovery.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we demonstrated the inhibitory effects of PLAG on tumors and tumor metastasis [45,46]. In addition, in severe inflammatory diseases due to excessive neutrophil infiltration, PLAG treatment provided symptom relief by regulating the movement of neutrophils to inflammatory lesions [47][48][49][50][51][52]. The ability of PLAG to regulate neutrophil infiltration and activity in tumor tissue enables the anti-tumor effect of aPD-L1 to be maximized so that cancer patients can make a complete recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study demonstrated that PLAG effectively alleviated the symptoms of oral mucosal inflammation caused by chemotherapy [ 24 , 25 ]. In addition, PLAG effectively alleviated symptoms of various inflammatory diseases induced by several factors [26] , [27] , [28] , [29] , [30] . In these papers, PLAG effectively regulated intracellular ROS, which prevented tissue damage caused by specific factors and suppressed severe inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study demonstrated that PLAG effectively alleviated the symptoms of oral mucosal inflammation caused by chemotherapy [ 24 , 25 ]. In addition, PLAG effectively alleviated symptoms of various inflammatory diseases such as acute lung injury (ALI), rheumatoid arthritis (RA), hepatitis, and gout [26] , [27] , [28] , [29] , [30] . Cisplatin treatment resulted in rapid weight loss and reduced food intake, which was mitigated in the PLAG co-treatment group.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the P2Y 1 -like receptor signaling pathway that promotes inflammation may exhibit an inhibitory effect on inflammation. For example, in a gout mouse model, the activation of the P2Y 6 receptors reduces 1-palmitoyl-2-linoleyl-3-acetyl-rac-glycerol-induced neutrophil infiltration, alleviating joint symptoms ( 55 ). Thus, the P2Y receptors play a complex role in inflammatory diseases, either as a friend or foe.…”
Section: Effect Of Purinergic Signaling Pathway On Gout Flaresmentioning
confidence: 99%